City of screens imagining audiences in Manila's alternative film culture - Trice, Jasmine Nadua (Durham, North Carolina Duke University Press, 2021)
"In City of Screens, Jasmine Nadua Trice examines the circulation of local and transnational alternative cinemas in early-2000s Metro Manila, Philippines. Trice considers how these circulations took shape in the wake of digital media piracy, the decline of the once-prolific, local commercial film industry, and the rise of an independent cinema movement heralded as a new national cinema both within the Philippines and abroad. The book focuses on sites of exhibition and distribution, including the pirated DVD district, the mall multiplex, and arthouse cinemas"--
Revanchist Cinemas and Bad Audiences, Multiplex Fiestas and Ideal Publics -- The Quiapo Cinematheque and Urban-Cinematic Authenticity -- Alternative Exhibition and the Rhythms of the City -- "Not For Public Exhibition" : Cinema Regulation, Alternative Cinema, and a Rational Body Politic -- "Hollywood Is Not Us" : National Circulation and the Speculative State.
Includes bibliographical references and index.
Keywords: Motion pictures -- Philippines -- Manila -- Distribution; Motion picture theaters -- Philippines -- Manila; Independent films -- Philippines -- Manila; Motion picture industry -- Philippines -- Manila